Genetic variations in microRNA-binding sites of solute carrier transporter genes as predictors of clinical outcome in colorectal cancer - Bendova, Petra; Pardini, Barbara; Susova, Simona; Rosendorf, Jachym; Levy, Miloslav; Skrobanek, Pavel; Buchler, Tomas; Kral, Jan; Liska, Vaclav; Vodickova, Ludmila; Landi, Stefano; Soucek, Pavel; et al. (Carcinogenesis, 2021)
One of the principal mechanisms of chemotherapy resistance in highly frequent solid tumors, such as colorectal cancer (CRC), is the decreased activity of drug transport into tumor cells due to low expression of important membrane proteins, such as solute carrier (SLC) transporters. Sequence complementarity is a major determinant for target gene recognition by microRNAs (miRNAs). Single-nucleotide polymorphisms (SNPs) in target sequences transcribed into messenger RNA may therefore alter miRNA binding to these regions by either creating a new site or destroying an existing one. miRSNPs may explain the modulation of expression levels in association with increased/decreased susceptibility to common diseases as well as in chemoresistance and the consequent inter-individual variability in drug response. In the present study, we investigated whether miRSNPs in SLC transporter genes may modulate CRC susceptibility and patient's survival. Using an in silico approach for functional predictions, we analyzed 26 miRSNPs in 9 SLC genes in a cohort of 1368 CRC cases and 698 controls from the Czech Republic. After correcting for multiple tests, we found several miRSNPs significantly associated with patient's survival. SNPs in SLCO3A1, SLC22A2 and SLC22A3 genes were defined as prognostic factors in the classification and regression tree analysis. In contrast, we did not observe any significant association between miRSNPs and CRC risk. To the best of our knowledge, this is the first study investigating miRSNPs potentially affecting miRNA binding to SLC transporter genes and their impact on CRC susceptibility or patient's prognosis.
Keywords: Organic Cation Transport Proteins; regulace genové exprese u nádorů; proteiny přenášející organické kationty; kolorektální nádory; Female; vazebná místa; ženské pohlaví; Neoplasm Recurrence, Local; jednonukleotidový polymorfismus; Gene Expression Regulation, Neoplastic; Colorectal Neoplasms; adjuvantní chemoterapie; lidé; 3' nepřekládaná oblast; Polymorphism, Single Nucleotide; messenger RNA; genetická predispozice k nemoci; studie případů a kontrol; následné studie; 3' Untranslated Regions; Genetic Predisposition to Disease; transportér organických kationtů 2; prognóza; RNA, Messenger; Computational Biology; Follow-Up Studies; Male; Case-Control Studies; Aged; Organic Anion Transporters; mikro RNA; lokální recidiva nádoru; Chemotherapy, Adjuvant; Prognosis; MicroRNAs; lidé středního věku; senioři; mužské pohlaví; přenašeče organických aniontů; výpočetní biologie; Organic Cation Transporter 2; Middle Aged; Binding Sites; Humans